Effects of sand-dust weather on wind speed fluctuation over near-surface of cotton fields in desert oasis area - Gao, Li; Cheng, Jianjun; Wu, Xiao; Pan, Zhouyang (Frontiers in Earth Science, 2025)
Strong wind and dusty weather are the main factors causing wind-sand disasters in cotton fields in desert oasis area. In order to investigate the effect of sand-dust weather on wind speed fluctuation over near-surface cotton fields, field observations of wind speed and direction were carried out using a two-dimensional ultrasonic anemometer, and the characteristics of wind speed fluctuation during clear-sky, blowing dust and sandstorm were analyzed. The results showed that the fluctuating wind speed at each height level increased with increasing height and wind speed in the three kinds of weather, with the fluctuation ranges being largest during sandstorms, followed by blowing dust, and smallest under clear-sky days. The correlation coefficient of fluctuating wind speed at each height level were all larger than 0.7, and the values at the heights of 1.5 and 2.0 m were all larger than 0.9, which indicated that there is a significant correlation between the fluctuating wind speed at each height. The wind speed fluctuation intensity is positively correlated with both height and average wind speed, the average values of fluctuation intensity in blowing dust and sandstorm are 1.375 and 2.33 times higher than those in the clear-sky days, respectively. Turbulence intensity decreases with the increase of height and average wind speed, and it is the smallest in the sandstorm. The results revealed the differential effects of extreme aeolian environments on the near-surface wind field in cotton fields, and provided a theoretical foundations for the prevention and control of wind and sand hazards in cotton fields in desert oasis.